Optimal Sample Preparation to Characterize Corrosion in Historical Photographs with Analytical TEM. (26th September 2014) - Grieten, Eva; Caen, Joost; Schryvers, Dominique
Abstract An alternative focused ion beam preparation method is used for sampling historical photographs containing metallic nanoparticles in a polymer matrix. We use the preparation steps of classical ultra-microtomy with an alternative final sectioning with a focused ion beam. Transmission electron microscopy techniques show that the lamella has a uniform thickness, which is an important factor for analytical transmission electron microscopy. Furthermore, the method maintains the spatial distribution of nanoparticles in the soft matrix. The results are compared with traditional preparation techniques such as ultra-microtomy and classical focused ion beam milling.